Does volatility matter? Expectations of price return and variability in an asset pricing experiment - Giulio Bottazzi; Giovanna Devetag; Francesca Pancotto (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
We present results of an experiment on expectation formation in an asset market. Participants to our experiment must provide forecasts of the stock future return to computerized utility-maximizing investors, and are rewarded according to how well their forecasts perform in the market. In the Baseline treatment participants must forecast the stock return one period ahead; in the Volatility treatment, we also elicit subjective confidence intervals of forecasts, which we take as a measure of perceived volatility. The realized asset price is derived from a Walrasian market equilibrium equation with non-linear feedback from individual forecasts. Our experimental markets exhibit high volatility, fat tails and other properties typical of real financial data. Eliciting confidence intervals for predictions has the effect of reducing price fluctuations and increasing subjects' coordination on a common prediction strategy.
Keywords: C91; C92; D84; G12; G14; 330; Experimental economics; Expectations; Coordination; Volatility; Asset pricing; CAPM; Erwartungstheorie; Volatilität; Experimentelle Ökonomik